Effective prediction of potential ferroptosis critical genes in clinical colorectal cancer - Huang, Hongliang; Dai, Yuexiang; Duan, Yingying; Yuan, Zhongwen; Li, Yanxuan; Zhang, Maomao; Zhu, Wenting; Yu, Hang; Zhong, Wenfei; Feng, Senling (Frontiers in Oncology, 2022)
Background: Colon cancer is common worldwide, with high morbidity and poor prognosis. Ferroptosis is a novel form of cell death driven by the accumulation of iron-dependent lipid peroxides, which is different from other programmed cell death mechanisms. Programmed cell death is a cancer hallmark, and ferroptosis is known to participate in various cancers, including colon cancer. The search for novel ferroptosis markers and mechanisms for targeted colon cancer therapy is necessary and urgent. To contribute to this, we performed a preliminary exploration of core ferroptosis genes in colon cancer to enable new treatment strategies. Methods: Genes associated with ferroptosis in colon cancer were obtained by data mining and screening for differentially expressed genes (DEGs) using bioinformatics analysis tools. We normalized the data across four independent datasets and a ferroptosis-specific database. The identified genes were validated by immunohistochemical analysis of pathological and healthy clinical samples. Results: We identified DEGs in colon cancer that are involved in ferroptosis. Among these, five core genes were found: ELAVL1, GPX2, EPAS1, SLC7A5, and HMGB1. Bioinformatics and immunohistochemistry analyses revealed that the expression of all five genes, except for EPAS1, was higher in tumor tissues than in healthy tissues. Conclusions: The preliminary exploration of the five core genes revealed that they are differentially expressed in colon carcinogenesis and play an essential role in ferroptosis in colon cancer. This study provides a foundation for subsequent research on ferroptosis in colon cancer, tumor drug resistance, and metastasis of cancer cells.